MeeChine / Ahmad Rusydi Harith Mohd Khair ... [et al.] - Mohd Khair, Ahmad Rusydi Harith; Ahmad Latif, Najihah; Zulkhairi, Muhammad Syamil; Ahmad Rosman, Ahmad Zafran; Muhammad Rosni, Muhammad Fauzan; Mohd Yusof, Muhammad Isa (2015)
MeeChine is a vending machine business based on a normal vending machine but it sells instant noodles instead. The vending machine remains one of the most used machines in the whole world as it provides the ability to buy things instantly. While the instant noodle being the all-time favourite to the Asian cultures, we decided to mix both of them in a machine. An instant noodle vending machine. Our business will be located at Lot G07, Ground Floor, Plæa Alam Sentral, Pusat Bandar, Seksyen 14, 40000 Shah Alam, Selangor, Malaysia. Our business are unique as there are a quite a few number of company setting vending machine, but as the seller of instant noodle vending machine. We aim to' offer -ouöproduct and services at competitive price to meet the demand of the low. to middle-income local market area residents. We will supply more vending machines at.campus. In addition,twe also provide regular replenishment of quality ingredients, cleaning, servicing and maintenance of vending as well as collection of sale proceeds to meet the needs of customer. With our; well known products, we believe it will benefit our clients in terms of service and quality. Moreover, we believe.that we-will This is because nowadays people in Malaysia are getting busiér day: by day; and écån'f get enough time make foods for themselves. Through the attention from the well-known products, our vending machine will surely gain most of the market share. We see that our business has the potential of success provide that is handled effectively and efficiently as the people always for food as a part of their life no matter where we are.